Brain tumor imaging with ALA - Stepp, Herbert; Schnell, Oliver (CRC Press, 2017)
Brain tumors have an average annual age-adjusted incidence in adults of 21-22 cases per 100,000 population. ey can be subdivided into primary brain tumors, which arise from glial or precursor cells of the brain itself, and secondary brain tumors or brain metastases, which originate from cancers outside the central nervous system (CNS). Brain metastases account for the majority of all malignant brain tumors (approximately 11/100,000/ year) and are almost twice as common as primary brain tumors, with an incidence rate of 6-7/100,000 per year (Ostrom et al., 2014). Due to their cellular origin, primary brain tumors are oen referred to as gliomas and the most common subtype, Glioblastoma multiforme (GBM), is also the most malignant primary brain tumor (15.7% of all tumors and 45.6% of malignant tumors). Despite extensive treatment with gross total tumor resection, radiochemotherapy followed by dierent salvage treatment options, its prognosis remains dismal, and the median overall survival is only 14-16 months (Stupp et al., 2005; Gilbert et al., 2013, 2014; Chinot et al., 2014).
CRIS-Team Scopus Importer:2023-09-13